QUALITY ASSESSMENT OF INTERPRETING OBAMA'S FAREWELL SPEECH (Journal of the College of Languages (JCL), 2018)
Interpreting is a process adopted by a skillful and well qualified interpreter to convey orally the meaning from a source language into a target language simultaneously .In this process the interpreter has no time to think or check the exact meaning of the words, phrases and sentences. The main technique used by the interpreter is based on his/her competence .This type of translation is used in press conferences and political speeches of high rank figures.This paper deals with analyzing the interpretation of Obama's farewell speech adopted by two authentic TV Channels(Sky News and AL- Jazeera).The aim of this paper is to investigate the quality of each interpreting by adopting Nida's (1996:164) four basic requirements of a successful translation as a model.This paper finds that the quality of interpreting of (AL-Jazeera TL2is more successful than (Sky newsTL1 )